PENGARUH SPESIALISASI AUDITOR DAN TENURE AUDIT TERHADAP KUALITAS AUDIT DENGAN FEE AUDIT SEBAGAI VARIABEL PEMODERASI - nuraini, sukmawati (JURNAL RISET AKUNTANSI TIRTAYASA, 2021)
This study aims to determine the effect of auditor specialization and temure audit of audit quality with audit fees as a moderating variable. Object this research on financial sector companies listed on the Stock Exchange Indonesia for the period 2016-2018. The technique used in sampling In this study, namely purposive sampling and then obtained 25 samples company. This study uses secondary data in the form of an annual report obtained from the Indonesia Stock Exchange (IDX). The analytical method used in This study is a multiple linear regression analysis. The results of this study indicate that: (1) Auditor specialization has no effect on audit quality. (2) Audit Temare has a positive effect on audit quality. (3) The audit fee cannot moderate the relationship between auditor specialization and audit quality. (4) Fee audit can moderate the relationship between audit tenure and audit quality.